Analisis Kemampuan Anak dalam Berbicara Menggunakan Metode Bercerita di TKIT Generasi Rabbani Kota Bengkulu - Sari, Eva Ria Indah; Ramadianti, Winda; Hartati, Merri Sri (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2024)
One of the first potentials that must be optimized in early childhood is the speaking aspect. However, in learning there is still a lack of children's ability to speak, especially to express, convey and communicate thoughts, and also the pronunciation of words is unclear. So children lack the courage to make their voices heard when telling stories. In this case it is also caused by the teacher's use of learning methods that are less attractive. The aim of this research was to see the influence of the storytelling method on children's speech development at TKIT Generasi Rabbani, Bengkulu City. The method used in this research is descriptive with a qualitative approach. The research implementation time is approximately one month, namely March 25 to April 29 2024. The research techniques used are interview techniques and observations of students. The results of the research show that the storytelling method has a great influence on children's speaking abilities and can increase children's self-confidence.